2017
DOI: 10.14218/erhm.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Chemical Sensitivity with Low Level Activation of Mechanotransduction Pathways in Hematologic Malignancies

Abstract: Large-scale screening has revealed that human hematopoietic cancer cell lines are generally more sensitive to various classes of drugs than cell lines established from solid tumors. A detailed examination of data in the Cancer Therapeutics Response Portal (http://portals.broadinstitute.org/ctrp/) suggests that this enhanced sensitivity is due to lower basal levels of activation of TAZ-TEAD mechanotransduction pathways in hematopoietic versus non-hematopoietic cells. Translation inhibitors such as omacetaxine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For instance, RP can affect the growth, senescence, apoptosis, invasion, radiation and drug therapy resistance of cancer cells through various mechanisms. Previous studies have revealed that both hematopoietic and non-hematopoietic cancer cell lines with increased RPL3 expression exhibit enhanced sensitivity to drugs ( 30 ), while the loss of RPL3 makes chemotherapy drugs ineffective ( 31 ). RPL3 can upregulate p21 expression at the transcriptional level ( 31 ), and participate in the cell response to chemotherapy, acting as a critical regulator of the cell cycle, apoptosis and DNA repair ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RP can affect the growth, senescence, apoptosis, invasion, radiation and drug therapy resistance of cancer cells through various mechanisms. Previous studies have revealed that both hematopoietic and non-hematopoietic cancer cell lines with increased RPL3 expression exhibit enhanced sensitivity to drugs ( 30 ), while the loss of RPL3 makes chemotherapy drugs ineffective ( 31 ). RPL3 can upregulate p21 expression at the transcriptional level ( 31 ), and participate in the cell response to chemotherapy, acting as a critical regulator of the cell cycle, apoptosis and DNA repair ( 31 ).…”
Section: Discussionmentioning
confidence: 99%